A brief guide to philosophical classics - Russell, James M. (Robinson, 2015)
A brief introduction to seventy-six of the most thought provoking books in history and how they can help us in our everyday lives. Big ideas sometimes come from the strangest places. In this wide ranging introduction, James M Russell takes the fear out of philosophy and selects seventy-six works - from Plato, Descartes and Wittgenstein to Philip K Dick and the Moomins as well as contemporary thinkers such as Peter Singer and John Rawls. Dividing into accessible sections, Russell gives us the lives as well as the lessons of the great thinkers, including a digest of their key ideas. A perfect antidote to the complex life.